Efficacy of hybrid therapy using prior administration of bepridil hydrochloride and cryoballoon ablation in patients with persistent atrial fibrillation. Issue 4 (April 2020) - Yakabe, Daisuke; Aso, Akemi; Araki, Masahiro; Murasato, Yoshinobu; Nakamura, Toshihiro
Highlights: Pulmonary vein isolation for persistent atrial fibrillation (PeAF) is controversial. We performed prior rhythm control with bepridil and cryoballoon ablation (CBA) for PeAF. At one-year, survival-free rate from AF was 78.5% after CBA. Refractoriness to bepridil and P-wave duration at CBA were associated with recurrence. Abstract: Background: Rhythm control before catheter ablation for persistent atrial fibrillation (PeAF) can improve clinical outcomes. We sought to investigate the efficacy of pretreatment with bepridil prior to cryoballoon ablation (CBA) with respect to clinical outcomes in patients with PeAF. Methods: We retrospectively analyzed 65 consecutive patients with PeAF who underwent CBA following pretreatment with bepridil hydrochloride (bepridil). Electrical cardioversion was additionally performed in cases involving failure of pharmacological sinus restoration before CBA. The primary endpoint was survival free from atrial tachyarrhythmia at the one-year follow-up, and the secondary endpoints were changes in P-wave morphology and left atrium diameter (LAD) before CBA. Results: At the one-year follow-up, 51 patients (78.5%) achieved the primary endpoint (non-recurrence group). Compared to the P-wave duration (Pdur) and dispersion at the time of sinus restoration, they significantly shortened at the time of CBA in the non-recurrence group, while they did not change in the recurrence group. There were no changes in LAD in both groups. Multivariate analysis revealed that refractoriness of bepridil ( p  = 0.03, odds ratio = 4.72, 95% confidence interval = 1.18–18.92), and longer Pdur at admission for CBA ( p  = 0.003, odds ratio = 1.08, 95% confidence interval = 1.01–1.14) were independent predictors of recurrence. Conclusions: Rhythm control with bepridil induced electrical reverse remodeling; bepridil may improve clinical outcomes after CBA.